Optimasi Parameter Proses 3D Printing Terhadap Transparansi Filamen Pla Menggunakan Metode Taguchi - Yeyen, Yeyen; Zulfitriyanto, Zulfitriyanto; Pristiansyah, Pristiansyah (Jurnal Inovasi Teknologi Terapan, 2024)
3D printing technology is the latest innovation in the world of technology. At the beginning of 3D Printing, technology was known as  additive layer. Fused deposition modeling (FDM) technology has been used as rapid prototyping or rapid prototyping with polymers. rapid prototyping with polymers with the material is a filament. filament. The working principle with the FDM step is the layer-by-layer method that uses components such as heat-erosion layer by layer method that uses components such as the heat-er nozzle in this section used to melt the filament that is heated in the process of making the 3D Printer prototype with Fused deposition modeling Ender model with a build size of 180 mm x 300 mm x 300 mm and a single nozzle is used to make research objects using a nozzle with a diameter of 0.4 mm. heater nozzle with a diameter of 0.4 mm, and the filament used is Polylactic Acid (PLA) which is 1.75 mm in diameter, the results of this test are to transparency test using a transparency testing tool, the Lux Meter. In this study using the Taguchi method to produce a more optimal response. where the process parameters such as nozzles, temperature, print speed, and print speed have been determined. temperature, print speed, bed temperature, layer thickness, and temperature-based plate in this study the resulting test Transparency level the highest was 223.667 and the lowest was 100.667 which is where this test using transparent PLA filament, the results of this study will be used for the manufacture of cup products.